Alnus glutinosa and Orientus ishidae (Matsumura, 1902) share phytoplasma genotypes linked to the 'Flavescence dorée' epidemics. (16th September 2021) - Rizzoli, Attilio; Belgeri, Elena; Jermini, Mauro; Conedera, Marco; Filippin, Luisa; Angelini, Elisa
Abstract: Flavescence dorée (FD) is a grapevine disease caused by associated phytoplasmas (FDp) which are epidemically spread by their main vector Scaphoideus titanus . The possible roles of alternative and secondary FDp plant hosts and vectors have gained interest in terms of better understanding of the FDp ecology and epidemiology. The findings of a survey conducted in the surroundings of three vineyards in the southern Swiss Alps aimed at studying the possible epidemiological role of the FDp secondary vector Orientus ishidae and the FDp host plant Alnus glutinosa are reported. This work demonstrates that O. ishidae is able to complete its biological cycle on A. glutinosa and to acquire FDp and 16SrV phytoplasmas very efficiently with an infection rate of 69% for the nymphal instars and 85% for the imagoes. A high prevalence of the map genotype M50 ( map type FD1), which is included in the S. titanus —grapevine epidemiological cycle, was found in O. ishidae and A. glutinosa . Additionally, M12 ( map type FD3), M44 and M47 were also sporadically detected. Surprisingly, the grapevines tested during this work were all infected by M54 ( map type FD2) only, while the few S. titanus caught in the vineyard canopy were all FDp free. In conclusion, the occurrence of infected common alder stands and O. ishidae nearby vineyards do not seem to play a prominent role in FD epidemics in southern Switzerland. Nevertheless, wild vegetation acts as a reservoir of the FDp inoculum, which may locally trigger a FD emergence if S. titanus populations are established inside vineyards.